ROLE OF OCIMUM SANCTUM ON NOISE STRESS INDUCED ALTERATIONS IN GLUCOCORTICOID AND CARBOHYDRATE METABOLISM - VELUSAMI DEEPIKA; R. SHEELA DEVI (International Journal of Pharma and Bio Sciences, 2013)
Noise is a common environmental stress factor that leads to alterations in plasma catecholamine, adrenocorticotropic hormone (ACTH) and cortisol concentrations. The countries are now a day’s interested in natural remedies, phytomedicines. In our present study we examined the effects of noise stress on glucocorticoid and glucose metabolism and the efficacy of ethanolic extract of Ocimum sanctum (OS) in preventing these alterations. Wistar albino male rats were divided into four groups-Groups I (Control), Group II (OS treated), Group III (stressed) and Group IV (OS pre treated and stressed). Noise stress for 15 days (100dB for 4hrs/ day) was given to the group III and IV and OS was injected to Group II and Group IV (100 mg/ kg bw. i.p). On the 16th day, animals were sacrificed and blood samples were analyzed for various biochemical parameters. In our study, corticosterone, glucose, insulin, glycogen phosphorylase levels and adrenal/body weight ratio were found to be significantly increased in the stressed group compared to the control and the levels of liver glycogen, muscle glycogen, glycogen synthase and thymus/body weight ratio were found to significantly decrease in the stressed group compared to the control. Our study showed that these alterations could be significantly reversed by OS.